THE STUDENTS’ DIFFICULTIES IN TRANSLATING ECONOMIC TERMS FROM ENGLISH INTO INDONESIAN - Saragih, Enni Erawati; Shofa, Fikrotus (ENGLISH JOURNAL, 2016)
This globalization era tends to ask people to be able to communicate globally; student needs a specific purpose in learning English. There are many terms in English need to be translated into Bahasa Indonesia such as economic terms; it needs to be understood by students in order to gain the meaning of the text. Along with the previous statement, the object of the research was to find out the difficulties in translating English-Indonesian of economic terminologies, especially common accounting terminologies. The aimed of the research was to find out kinds of procedure and the difficulties that students use in translating accounting terms from English into Indonesian. Quantitative method was applied in this research. The samples were 6 students coming from the highest, medium and lowest GPA. The instrument was written test and questionnaire. The writer found that some participants failed in providing a correct equivalent for each term, but some participants could provide the terms by using a suitable procedure of translation to maintain the meaning. The analysis of the data confirms that students? mistakes were due to the meaning of the SL was not worth into the language of the recipient, and then it raised an ambiguity. Most of the students used adaptation and borrowing procedures in their translation. There was nothing wrong in the use of any procedure since it carries the meaning. The difficulties came from four such as Lack of cultural understanding in the economic itself, lack of special concern in English, lack of students' understanding on some economics lecturing and lack of the wealth in English vocabulary. So based on finding it could be assumed that teachers or lectures are expected to use various methods in order to attract student?s proclivity to study.